2006
DOI: 10.1002/bip.20486
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sequential oligopeptide carriers on the bioactive structure of conjugated epitopes: Comparative study of the conformation of a Herpes simplex virus glycoprotein gD‐1 epitope in the free and conjugated form, and protein “built‐in” crystal structure

Abstract: Synthetic carriers play an important role in immunogen presentation, due to their ability of inducing improved and specific responses to conjugated epitopes. Their influence on the bioactive conformation of the epitope, though admittedly crucial for relevant in vitro and in vivo applications, is difficult to evaluate, given the usual lack of information on the complex conformational features determined by the nature of the carrier and the mode of ligation. Using the Herpes simplex virus glycoprotein D-1 epitop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Multimerization has long been recognized as an effective strategy for enhancing the response of peptides in immunization experiments1–3. Among the different approaches such as simple polymerization4, or conjugation to sequential oligopeptide carriers2, 5, or display on lysine scaffolds6, 7, incorporation into dendrimeric systems such as the MAP platforms pioneered by Tam1, 8, 9 has proven particularly successful for immunological and microbiological applications9–12.…”
Section: Introductionmentioning
confidence: 99%
“…Multimerization has long been recognized as an effective strategy for enhancing the response of peptides in immunization experiments1–3. Among the different approaches such as simple polymerization4, or conjugation to sequential oligopeptide carriers2, 5, or display on lysine scaffolds6, 7, incorporation into dendrimeric systems such as the MAP platforms pioneered by Tam1, 8, 9 has proven particularly successful for immunological and microbiological applications9–12.…”
Section: Introductionmentioning
confidence: 99%
“…It was also determined that in the case of OT20-conjugate the C-terminus attachment site of the epitope was more flexible than in the case of SOC conjugate. 19 In the present study, the influence of carriers on the antibody recognition of a much shorter epitope, Ab(4-10), was investigated by preparation of OT20, MAP, and SOC conjugates. The key feature of these oligopeptide carriers is the amplification of the epitope peptide in a well-defined manner, all conjugates containing four copies of the Ab(4-10) epitope attached to the carrier either through the N-or C-terminus.…”
mentioning
confidence: 99%
“…Another epitope of gD-1 has been identified by monoclonal antibodies and located in the 268-287 region (19,20). It was shown that the minimal epitope of this region in the HSV gD-1 was the important in the immunological recognition, as has been proven in the case of another sequence of the same protein (22).…”
Section: Introductionmentioning
confidence: 94%